(untitled) (Journal of Global Accounting, 2025)
The study evaluated the effect of Forensic Audit skills on fraud control in Ministries, Departments and Agenncies in the South East Nigeria. Specifically, the study ascertained the effect of forensic arbitration skills on fraud control in Ministries, Departments and Agencies in South-East, Nigeria. It also investigated the effect of forensic litigation skills on fraud control in Ministries, Departments and Agencies in South-East, Nigeria. Deploying the survey research design, a total of 260 Respondents was determined using Yaro Yamanene formula and sampled in MDAs in the 5 States namely Anambra, Abia, Ebonyi, Enugu, and Imo States which constitute the South East region of Nigeria. A 5-point rating scale well articulated google form-based research e-questionnaire served as the channel for the harvest of opinion from the Respondents. The Multiple regression analytical technique was used to test the relevant hypotheses, and the study found that that forensic arbitration skills have a significant and positive effect on fraud control (coefficient 0.382; p-value 0.0000). It further discovered that forensic litigation skills significantly and positively affect fraud control in MDAs (coefficient 0.241; p-value 0.0000). Based on these results, the study concludes that. a systemic linkage where the application of forensic capabilities not only influences the perception and management of fraud but also integrally tied to broader organizational integrity mechanisms is existent. The study therefore recommends that the Directors of Internal Audit in MDAs need to formulate and implement internal fraud control policies that utilize forensic arbitration methods—such as expert-led hearings and negotiated settlements—to swiftly resolve suspected fraud cases, reduce operational disruptions, and enhance compliance culture. Also, the Chairman of the Economic and Financial Crimes Commission (EFCC) should collaborate with the judiciary to create fast-track courts for fraud-related litigation supported by forensic audit evidence, ensuring timely adjudication and stronger fraud control outcomes in the public sector.